Is it possible to “find space for mental health” in young people? effectiveness of a school-based mental health literacy promotion program - Campos, Luísa (2018)
Lack of knowledge regarding, and the stigma associated with, mental disorders have been identified as major obstacles for the promotion of mental health and early intervention. The present study aimed to evaluate the effectiveness of a school-based intervention program focused on the promotion of mental health literacy (MHL) in young people (“Finding Space for Mental Health”). A sample of 543 students (22 classes), aged between 12 and 14 years old, participated in the study. Each class of students was randomly assigned to the control group (CG; n = 284; 11 classes) or the experimental group (EG; n = 259; 11 classes). MHL was assessed using the Mental Health Literacy questionnaire (MHLq), which is comprised of three dimensions—Knowledge/Stereotypes, First Aid Skills and Help Seeking, and Self-Help Strategies. The scores on these dimensions can also be combined to give an overall or total score. Participants from the EG attended the MHL promotion program (two sessions, 90 min each) delivered at one-week intervals. Sessions followed an interactive methodology, using group dynamics, music, and videos adapted to the target group. All participants responded to the MHLq at three points in time: pre-intervention assessment (one week prior to the intervention), post-intervention assessment (one week after the intervention) and follow-up assessment (six months after the intervention). The intervention effectiveness and the differential impact of sociodemographic variables on the effectiveness of the program were studied using a Generalized Estimation Equation (GEE). Results revealed that participants from the EG demonstrated, on average, significantly higher improvement in MHL from pre-intervention to follow-up when compared to participants from the CG. Different sociodemographic variables affected the effectiveness of the program on distinct dimensions of the MHLq. Overall, “Finding Space for Mental Health” showed efficacy as a short-term promotion program for improving MHL in schools.